A pilot search for extragalactic OH absorption with FAST. Issue 3 (1st October 2020) - Zheng, Zheng; Li, Di; Sadler, Elaine M; Allison, James R; Tang, Ningyu
ABSTRACT: OH absorption is currently the only viable way to detect OH molecules in non-masing galaxies at cosmological distances. There have been only six such detections at z > 0.05 to date and so it is hard to put a statistically robust constraint on OH column densities in distant galaxies. We carried out a pilot OH absorption survey towards eight associated and one intervening H i 21-cm absorbers using the Five-hundred-meter Aperture Spherical radio Telescope (FAST). We were able to constrain the OH abundance relative to H i ([OH]/[H i ]) to be lower than 10 −6 ∼ 10 −8 for redshifts z∈ [0.1919, 0.2241]. Although no individual detection was made, stacking three associated absorbers free of RFI provides a sensitive OH column density 3σ upper-limit $\sim 1.57 × 10^{14} (T_x^{\rm OH}/10\, K)(1/f_ c^{\rm OH}) cm^{-2}$, which corresponds to a [OH]/[H i ] < 5.45 × 10 −8 . Combining with archival data, we show that associated absorbers have a slightly lower OH abundance than intervening absorbers. Our results are consistent with a trend of decreasing OH abundance with decreasing redshift.